Ø¢ÙØ§ÙÛØ² Ø¨ÙØ§Û Ø¹ÙÙØ§ Ø¯Ø± Â«Ø±Ø¬ÙØ¹ Ø¬Ø§ÙÙ Ø¨Ù Ø¹Ø§ÙÙÂ» Ø¨Ù Ø±ÙØ´ Â«Ø±ÙØªØ§Ø±Ø´ÙØ§Ø³ÛÂ» Ù ÙÙØ§ÛØ³Ù Ø¢Ù Ø¨Ø§ Â«Ø±Ø¬ÙØ¹ ÙÙÙÙØ¯ Ø¨Ù ÙØ±Ø¬Ø¹ ØªÙÙÛØ¯Â» - Ã˜Â¹Ã™Â„Ã›ÂŒÃ˜Â¯Ã™ÂˆÃ˜Â³Ã˜Âª, Ã˜Â§Ã˜Â¨Ã™ÂˆÃ˜Â§Ã™Â„Ã™Â‚Ã˜Â§Ã˜Â³Ã™Â…; Ã˜Â´Ã›ÂŒÃ˜Â±Ã˜Â§Ã˜Â²Ã›ÂŒ, Ã˜Â³Ã›ÂŒÃ˜Â¯ Ã˜Â±Ã˜Â¶Ã˜Â§ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
Given that the most principle reason for imitation (taqlÄ«d) is the intellectual basis in âthe reference of the ignorant to the learnedâ and, in one respect, reliance on oneâs personal conjectures and bringing up an âintellectual basisâ claim without (presenting) valid document on this subject has become a source of incorrect judgments, it is attempted in this article to delve into âthe intellectual basis in the reference of the ignorant to the learnedâ through exploring the methods of acquiring the intellectual basis with the use of behavioristic method. The outcome achieved includes instances such as: distinction between âreference to the specialistâ and âreference of the ignorant to the learnedâ, and regarding the needs of collective living and personal certainty as the source for the appearance of such sÄ«ra by the jurists. And finally, by analyzing the term taqlÄ«d (imitation from legal authority) in jurisprudence and principles and comparing the outcomes resulting from behaviorism with âreference of the ignorant to the legal authorityâ, what can be attributed to the attitude of the intellectual is the no-devotional reference of the client (the referring person), which is something other than the connotative taqlÄ«d